Pandemic influenza A(H1N1) 2009 virus outbreak among boarding school pupils in Madagascar: compliance and adverse effects of prophylactic oseltamivir treatment - Soatiana Rajatonirina; Jean-MicheI Heraud; Laurence Randrianasolo; Norosoa Razanajatovo; Tombo Ramandimbisoa; Maherisoa Ratsitorahina; Vincent Richard (Journal of Infection in Developing Countries)
Introduction: In October 2009, the first outbreak of pandemic influenza A(H1N1) 2009 virus  in Madagascar occurred at a school in Antananarivo. Among the first 12 cases, five were reported in boarding pupils at the school. The school closed 10 days into the outbreak. Mass oseltamivir prophylactic treatment was used to contain the outbreak. This study aimed to determine the transmission of infection among boarding school pupils and to evaluate the adverse effects of oseltamivir chemoprophylactic treatment and their impact on compliance.